A case of the management of Heterotopic ossification as the result of acetabular fracture in a patient with traumatic brain injury. (2015) - Rollo, Giuseppe; Pellegrino, Marco; Filipponi, Marco; Falzarano, Gabriele; Medici, Antonio; Meccariello, Luigi; Bisaccia, Michele; Piscitelli, Luigi; Caraffa, Auro
Highlights: We reviewed a case of a patient suffering from heterotrophic ossification. We reasoned about possible etiologies and surgical heterotrophic ossification. We reasoned on which therapy to use the aid to surgery. This case gives us a review of the scientific literature. Abstract: Introduction: The most common location of the heterotopic ossification is represented by the pelvic ring, followed by the elbow, shoulder, and knee. In the case of severe brain or spinal traumas resulting from a coma state, calcifications developed within three months from the trauma, and occurred more frequently in people between twenty and thirty years of age. Presentation of case: We present a case report of a 29-year-old patient with heterotopic ossification of the left side hip soft tissue, as a result of traumatic brain injury (coma for ten days). The patient suffered by fracture of the iliac wing, acetabulum and left ischio pubic ramus, which were surgically treated. The patient came to our observation for hip stiffness six months prior to the study. XR performed in standard projections, wing and obturator, showed the formation of a grade 3 heterotopic ossification of Brooker's classification. From the post-surgery to sixth month after the demission, the patient was surgically treated by an anterolateral hip approach to remove calcifications. The patient was subjected to anti-inflammatory therapy and indomethacin, shock waves, and physiotherapy to improve the mobilization of the hip. He had good results. Discussion and conclusion: Heterotopic ossification represents a disease which is not very common, but has particular characteristics with debilitating consequences. The disease is responsible for reduction of functionality of the affected joint. There are many different treatments available, but it is necessary to choose the most appropriate one, considering: responsible cause, location, Brooker's classification, the articular functionality.